2009
DOI: 10.4076/1757-1626-2-6707
|View full text |Cite
|
Sign up to set email alerts
|

Hypernatremia secondary to soluble paracetamol use in an elderly man: a case report

Abstract: IntroductionSoluble (effervescent) paracetamol is routinely given to elderly patients for convenience. A daily dose of 4 gm in this soluble formulation can contain up to 8.7 gm of sodium chloride, which exceeds the threshold recommended by the World Health Organization. Hypernatremia secondary to soluble paracetamol has rarely been reported. We describe an elderly patient who developed hypernatremia shortly after taking soluble paracetamol.Case presentationA confused 89-year-old man with back pain secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In comparison to other foods that are considered high in salt, 8 effervescent paracetamol 500 mg tablets contain nearly twice the amount of salt than 100 g of bacon [50]. In view of the elevated sodium levels in these products, there have been published case reports linking soluble paracetamol to hypertension [51], and hypernatraemia [52]; a further nested case controlled study using the Clinical Practice Research Datalink (CPRD) showed that exposure to sodium-containing effervescent formulations was positively -and significantlyassociated with increased odds of adverse cardiovascular events [53].…”
Section: The Challenges Of Multimorbidity and Drug Delivery In An Older Populationmentioning
confidence: 99%
“…In comparison to other foods that are considered high in salt, 8 effervescent paracetamol 500 mg tablets contain nearly twice the amount of salt than 100 g of bacon [50]. In view of the elevated sodium levels in these products, there have been published case reports linking soluble paracetamol to hypertension [51], and hypernatraemia [52]; a further nested case controlled study using the Clinical Practice Research Datalink (CPRD) showed that exposure to sodium-containing effervescent formulations was positively -and significantlyassociated with increased odds of adverse cardiovascular events [53].…”
Section: The Challenges Of Multimorbidity and Drug Delivery In An Older Populationmentioning
confidence: 99%